Asian yearbook of international law. - Chimni, B. S., 1952-; Masahiro, Miyoshi; Subedi, Surya P., 1958- (Asian yearbook of international law, 2005)
The Asian Yearbook of International Law is a major refereed publication dedicated to international law issues as seen primarily from an Asian perspective.